2017
DOI: 10.1037/cep0000130
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan changes in attention revisited: Everyday visual search.

Abstract: This study compared visual search under everyday conditions among participants across the life span (healthy participants in 4 groups, with average age of 6 years, 8 years, 22 years, and 75 years, and 1 group averaging 73 years with a history of falling). The task involved opening a door and stepping into a room find 1 of 4 everyday objects (apple, golf ball, coffee can, toy penguin) visible on shelves. The background for this study included 2 well-cited laboratory studies that pointed to different cognitive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
2
22
0
2
Order By: Relevance
“…This paper reports on the first large developmental study of unique object search. Note that Brennan, Bruderer, Liu-Ambrose, Handy, and Enns (2017) did quite a large life-span study in which observers actually searched in a real room for real objects, although their study was not directly designed to test developmental changes; they only tested children of about 6 and 8 years of age. In our study, the aim is to compare different developmental changes from 4 to 25 years of age in a large sample of participants (293) to track the time course of cognitive processes immersed in a unique real-world object search.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reports on the first large developmental study of unique object search. Note that Brennan, Bruderer, Liu-Ambrose, Handy, and Enns (2017) did quite a large life-span study in which observers actually searched in a real room for real objects, although their study was not directly designed to test developmental changes; they only tested children of about 6 and 8 years of age. In our study, the aim is to compare different developmental changes from 4 to 25 years of age in a large sample of participants (293) to track the time course of cognitive processes immersed in a unique real-world object search.…”
mentioning
confidence: 99%
“…This is often taken to show immaturity in the development of topdown attentional control processes (Donnelly et al, 2007;Merrill & Conners, 2013;Michael et al, 2013;Trick & Enns, 1998;Woods et al, 2013). But some studies have found that differences between adults and children were not that large (Hommel et al, 2004) or may depend on motivational factors: Brennan et al (2017) found that differences between children and young adults disappeared when the target was a toy penguin that might be intrinsically interesting to children. The diversity of results may have several causes.…”
mentioning
confidence: 99%
“…A related limitation is that we only examined young adults. Older adults are often slower and less accurate at locating objects in cluttered scenes . In future, it would therefore be helpful to collect additional normative data for older adults performing the Search task.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are often slower and less accurate at locating objects in cluttered scenes. [68][69][70] In future, it would therefore be helpful to collect additional normative data for older adults performing the Search task. There may also be age-related changes in performance on the Faces test also.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Conjunction search trials have been found to be more sensitive than single feature search paradigms at eliciting iASD and non-iASD group differences in performance (e.g., Kaldy et al, 2011 ; O’Riordan, 2000 ; O’Riordan, Plaisted, Driver, & Baron-Cohen, 2001 ; Plaisted et al, 1998 ). Further, single feature search performance plateaus by approximately 2 years of age, typically, while conjunction search performance continues to develop throughout childhood and adolescence ( Brennan, Bruderer, Liu-Ambrose, Handy, & Enns, 2017 ; Donnelly et al, 2007 ; Woods et al, 2013 ). Considering the chronological age and developmental level of our participants, it was deemed more appropriate to examine conjunction search performance in the current study.…”
Section: Methodsmentioning
confidence: 99%